Ion Beam Irradiation-Induced Amorphization of Nano-Sized KxLnyTa2O7-v Tantalate Pyrochlore - Lu, Fengyuan; Shen, Yiqiang; Dong, Zhili; Wang, Gongkai; Zhang, Fuxiang; Ewing, Rodney C.; Lian, Jie (Frontiers in Energy Research, 2014)
Nano-sized (~10–15 nm) tantalate pyrochlores KxLnyTa2O7-v (Ln = Gd, Y, and Lu) were irradiated with 1 MeV Kr2+ beams at different temperatures and their radiation response behaviors were studied by in situ transmission electron microscopy observations. All of these nano-sized KxLnyTa2O7-v pyrochlores are sensitive to radiation-induced amorphization with low-critical doses (~0.12 dpa) at room temperature and high-critical amorphization temperatures above 1160 K. The K+ plays a key role in determining the radiation response of tantalate pyrochlores, in which the K+-rich KLuTa2O7 displays greater amorphization susceptibility than K0.8GdTa2O6.9 and K0.8YTa2O6.9 with lower K+ occupancy at the A-site. The reduced amorphization tolerance of the composition with a greater K+ content is consistent with the prominently larger K+/Ta5+ cationic radius ratio, which may result in more structural deviation from the parent fluorite structure and less capability to accommodate radiation-induced defects. An empirical correlation between critical amorphization temperature and ionic size was derived, generally describing the dominant effect of the cation ionic size in controlling radiation response of a wide range of pyrochlore compounds as potential nuclear waste forms. The results of the tantalate pyrochlore in this work highlight that nanostructured pyrochlores are not intrinsically radiation tolerant and their responses are highly compositional dependent.